Analisis Penggunaan Konsumsi Bahan Bakar (Fuel Consumption) terhadap Variable Taxi Time (Taxiway) Pesawat di Bandara Internasional Juanda Surabaya - Mahmudah, Siti Hidayatul; Tamara, Amelia Puspa (Jurnal Ground Handling, 2025)
Aircraft movement is divided into 2 parts, namely land side and air side movements. Activities in the airside area of Juanda International Airport Surabaya have quite dense traffic both in the morning, afternoon, or evening. Aircraft operational activities on land, especially during the taxiing phase, are one of the factors that contribute to the course of flights that require significant fuel. This study aims to analyze the effect of fuel consumption on the variable taxi time of aircraft at Juanda International Airport Surabaya. The main focus of this study is to identify the extent to which the taxiing process affects the amount of fuel consumed by the A320 aircraft before taking off. This study uses a descriptive quantitative approach with observation methods and secondary data collection on 79 aircraft of various types, namely Airbus A320, Boeing 737-900 (B739), Airbus A330-900 (A339), and Airbus A320neo (A20N) operating at Juanda International Airport Surabaya. The data collected includes taxiing duration and estimated fuel consumption during the process. The analysis was conducted to determine the correlation between taxiing duration and the amount of fuel used, as well as to identify other factors that affect the efficiency of movement on the taxiway. The results of this analysis indicate that there is a positive relationship between taxiing time and fuel consumption, where the longer the aircraft performs the taxiing process in the taxiway area, the greater the fuel consumed. These results indicate the importance of optimizing aircraft movement management on the ground, both in terms of taxiway lane arrangements and aircraft departure and arrival scheduling, in order to reduce excessive fuel use.